Percutaneous microwave ablation of renal cell carcinoma using a high power microwave system: focus upon safety and efficacy. (3rd October 2018) - Filippiadis, D. K.; Gkizas, C.; Chrysofos, M.; Siatelis, A.; Velonakis, G.; Alexopoulou, E.; Kelekis, A.; Brountzos, E.; Kelekis, N.
Abstract: Objectives: Percutaneous ablation is an expanding, minimally invasive approach for small- to medium-sized renal masses. The purpose of this study is to review safety, and mid-term efficacy of percutaneous microwave ablation (MWA) for Renal Cell Carcinoma (RCC) treatment using a high power microwave system. Methods and materials: Institutional database research identified 50 consecutive patients with a single lesion resembling renal cell carcinoma in CT and MRI who underwent percutaneous microwave ablation using a high power microwave system. All patients underwent biopsy on the same session with ablation using an 18G semi-automatic soft tissue biopsy needle. Contrast-enhanced computed tomography or magnetic resonance imaging was used for post-ablation follow-up. Patient and tumour characteristics, microwave technique, complications and pattern of recurrence were evaluated. Results: Mean patient age was 74 years (male–female: 31–19). Average lesion size was 3.1 cm (range 2.0–4.3 cm). Biopsy results report RCC ( n = 48), inflammatory myofibroblastic tumour ( n = 1), and non-diagnostic sample ( n = 1). The 3-year overall survival was 95.8% (46/48). Two patients died during the 3-year follow-up period due to causes unrelated to the MW ablation and to the RCC. Minor complications including haematomas requiring nothing but observation occurred at 4% (2/50) of the cases. Local recurrence of 6.25% (3/48) was observed with 2/3 cases being re-treated achieving a total clinical success of 97.9% (47/48 lesions). Conclusions: Percutaneous microwave ablation of RCC using a high power microwave system is a safe and efficacious technique for the treatment of small- to medium-sized renal masses.